Thinking Styles of Science Teachers in Relation to Certain Variables: A Descriptive Study”" (Journal of the College of Basic Education, 2025)
This research aims to identify the thinking styles among science teachers in light of some variables (a survey study). The research sample consisted of 300 teachers of both genders, selected randomly. The researcher applied the "Harrison-Bramson" thinking styles scale, which includes 13 situations with five items each. The scale demonstrated good reliability and validity. The results showed that science teachers tend to have a realistic thinking style according to the Harrison-Bramson scale. Additionally, there were no statistically significant differences between genders in the demographic variables. Based on these findings, the researcher provided a set of recommendations and suggestions